Providing oral care for adults with mental health disorders: Dental professionals' perceptions and experiences in Perth, Western Australia. Issue 1 (8th October 2018) - Scrine, Clair; Durey, Angela; Slack‐Smith, Linda
Abstract: Objective: To explore dental professionals' perceptions and experiences of providing oral health care for adults with mild to moderate mental health disorders (MHD) in Perth, Western Australia. Methods: A grounded theory approach guided this research which comprised semi‐structured interviews with oral health professionals working in private and/or public dental facilities attended by adults with MHD. An iterative analysis of transcripts identified emerging issues that were organized into categories under which key themes were noted, coded, compared, discussed, reviewed and revised independently by two researchers to ensure rigour. Results: Sixteen interviews were conducted with six general dentists, three dental specialists, four oral health therapists (OHT) and three dental assistants. Barriers to providing oral health care for adults with MHD included limitations of the current model of care, often focused on treating advanced disease; limited inter‐professional collaboration; an over‐burdened public dental system and the financial constraints of private practice. Personal barriers included perceptions that people with MHD had limited capacity for self‐care and preventing oral disease. Factors that would enable oral health care included training and professional development for dental professionals to work effectively with people with MHD and a more flexible, inter‐professional approach that involved prevention and inviting family to consultations about oral health in primary health care settings. Conclusions: Our study reveals structural barriers where services often appear to be inadequately prepared to meet the oral health needs of people with MHD. This suggests the need for strategies to review current models of care and encourage and support dental professionals to provide oral health care that is inclusive, inter‐professional, focused on prevention and sensitive to the social context and lived experience of people with MHD.